Pengaruh Motivasi dan Disiplin terhadap Kinerja Karyawan Tata Usaha dan Guru di SMKS Muhammadiyah 1 Sintang - Irfan Maulana; Kristiana Sri Utami (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study was conducted on employees of SMKS Muhammadiyah 1 Sintang with the aim of identifying the influence of motivation and discipline on employee performance. A quantitative research method was used with data analysis through the SPSS program. The research population consisted of administrative staff and teachers at SMKS Muhammadiyah 1 Sintang, with a sample of 40 respondents selected using the total sampling method. Data collection techniques used an online questionnaire, and the research instrument employed a Likert scale. Data analysis methods included validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. The results of this study indicate that: 1. Based on descriptive analysis, the motivation variable had an average value of 4.36 (very high category), the discipline variable 4.44 (very high category), and the performance variable 4.31 (very high category). 2. Motivation (X1) does not have a significant positive effect on employee performance (Y) with a calculated t-value of 1.631. 3. Discipline (X2) has a significant positive effect on employee performance (Y) with a calculated t-value of 2.871. Motivation (X1) and Discipline (X2) together have a significant effect on employee performance with a significance value of 0.000 < 0.05 and a calculated F value (12.129) > table F value (4.10).